The animal naming test: An easy tool for the assessment of hepatic encephalopathy. Issue 1 (27th May 2017) - Campagna, Francesca; Montagnese, Sara; Ridola, Lorenzo; Senzolo, Marco; Schiff, Sami; De Rui, Michele; Pasquale, Chiara; Nardelli, Silvia; Pentassuglio, Ilaria; Merkel, Carlo; Angeli, Paolo; Riggio, Oliviero; et al.
Abstract : Screening for hepatic encephalopathy (HE) that does not cause obvious disorientation or asterixis (minimal HE [MHE]/grade 1 HE) is important. We examined if the animal naming test (ANT1 ) (maximum number of animals listed in 1 minute) is useful in this context. In total, 208 healthy controls, 40 controls with inflammatory bowel disease, and 327 consecutive patients with cirrhosis underwent the ANT1 . Patients were tested for MHE by the psychometric HE score, and 146 were assessed by electroencephalography; 202 patients were followed up regarding the occurrence of overt HE and death. In the healthy controls, ANT1 was influenced by limited education (<8 years) and advanced age (>80 years, P < 0.001). Using an age and education adjusting procedure, the simplified ANT1 (S‐ANT1 ) was obtained. An S‐ANT1 of <10 animals was abnormal. Of the patients, 169 were considered unimpaired, 32 as having HE ≥grade 2, and 126 as having MHE/grade 1 HE. This group had lower S‐ANT1 than unimpaired patients (12 ± 0.4 versus 16 ± 0.7, P < 0.001) and higher S‐ANT1 than those with HE ≥grade 2 (4 ± 0.9). In grade 1 HE the S‐ANT1 was lower than in MHE. Following receiver operating characteristic analysis (Youden's index), 15 animals produced the best discrimination between unimpaired and MHE/grade 1 HE patients. Thus, a three‐level score (0 for S‐ANT1 ≥15, 1 for 10 ≤ S‐ANT1 < 15, 2 for S‐ANT1 <10) was obtained. This score was correlated both to the psychometric HE score ( P < 0.0001) and to electroencephalography ( P = 0.007). By sample random split validation, both S‐ANT1 and its three‐level score showed prognostic value regarding the 1‐year risk of overt HE and death. No inflammatory bowel disease control had S‐ANT <15. Conclusion : The S‐ANT1 is an easily obtainable measure useful for the assessment of HE. (Hepatology 2017;66:198–208).